Li2TiO3/Graphene and Li2TiO3/CNT Composites as Anodes for High Power Li–Ion Batteries. Issue 31 (22nd August 2018) - Lakshmi‐Narayana, Ambadi; Dhananjaya, Merum; Guru‐Prakash, Nunna; Hussain, Obili M.; Mauger, Alain; Julien, Christian M.
Abstract: Three‐dimensional composites Li2 TiO3 /graphene (LTO/Gr) and Li2 TiO3 /carbon nanotube (LTO/CNTs) were synthesized by solid‐state reaction for application as anode materials for lithium‐ion batteries. These composites are structurally characterized by X‐ray diffraction, Raman spectroscopy and high‐resolution transmission electron microscopy, while electrochemically tests are performed by cyclic voltammetry and chronopotentiometry. The synergetic effect of graphene and CNTs with LTO facilitate the network conduction leading to faster electron and Li + ion transfer and improve cycling stability and rate capability of the anode. The LTO/Gr and LTO/CNTs composites exhibited an initial discharge capacity as high as 154 and 149 mAh g −1 at 1C rate, respectively and retained excellent cycling stability of 98% and 96% after 30 charge–discharge cycles. Abstract : Li2 TiO3 /graphene and Li2 TiO3 /carbon‐nanotube nanocomposites were prepared by solid‐state reaction. The homogenous and stable structures afford a highly conductive matrix for Li‐ion insertion into LTO nanoparticles and reduces the lithium ion and electron transport diffusion resistances. Li2 TiO3 /graphene used as anode of lithium cell exhibits a high capacity of 154 mAhg −1 at 1C rate and excellent cyclability.